Studies on flow performance of crude palm oil in transportation handling using different type of mechanisms - Nurul Haizan, Ahmad (2010)
Crude palm oil (CPO) has high tendency to solidify. This drawback has make the CPO become solidify in the pipelines and will cause loss of millions of ringgit per year. The objectives of this research were to identify suitable temperature condition for best flow performance of CPO (least frictional force exists) and to identify physical parameter to create resonance frequency using ultrasonic equipment. There are two methods that were employed for the improvement of the CPO in transportation handling which are by using jacketed steam and ultrasonic equipment. This work reports viscosity data, determined with viscometer for CPO over the temperature range of 30ºC - 60ºC and also the viscosity data that was determined for CPO over the ultrasonic frequency of 3MHz, 6MHz and 9MHz. From the result obtained, the viscosity of the CPO decreases nonlinearly with increasing temperature as has been found in other ordinary liquids. Then, all solid CPO were observed to be totally dissolved at temperature 50ºC. By using ultrasonic equipment, the result shows that viscosity decreases approximately linearly with increasing ultrasonic frequency at constant temperature. All the methods used shows satisfactory results, where the flow of the CPO in transportation handling will increase. The research findings shall ease problems to CPO transporter or pipeline users and it would contribute significantly in cost reduction of CPO storage and handling.